Misiologi Diaspora: Sebuah Proposal untuk Menjawab Fenomena Perpindahan Penduduk di Indonesia - Jonathan Wijaya (Kharisma: Jurnal Ilmiah Teologi, 2023)
Abstract Until now, population movement is a phenomenon that cannot be stopped anymore. Data released by the International Organization for Migration (IOM) shows that 281 million people are migrants in the world in 2020. In Indonesia, the Indonesian Statistics Agency (BPS) records that 13.2% of Indonesia's population are migrants in 2019. Author's question, Are there opportunities for Christian missions in responding to the phenomenon of population movement in Indonesia? What form does this mission take? By analyzing the literature, the author will propose a diaspora missiology for evangelizing to people of different religions and ethnicities where this mission focuses more on evangelizing those who can be reached in areas around Indonesian Christians. That way, people who are evangelized can become effective missionaries to reach their tribe and other tribes. However, diaspora missiology does not ignore the responsibility of Indonesian Christians to bring the Gospel to the place where their diaspora is located. Abstrak Sampai dewasa ini, perpindahan penduduk menjadi fenomena yang tidak dapat dibendung lagi. Data yang dikeluarkan oleh Organisasi Internasional untuk Migrasi (IOM) menunjukkan bahwa 281 juta orang merupakan migran di dunia pada tahun 2020. Di Indonesia, Badan Statistik Indonesia (BPS) mencatat bahwa 13,2% penduduk Indonesia adalah migrasi pada tahun 2019. Pertanyaan penulis, apakah ada peluang misi Kristen di dalam merespons fenomena perpindahan penduduk di Indonesia? Bagaimana bentuk misi tersebut? Dengan analisis literatur, penulis akan mengusulkan misiologi diaspora untuk penginjilan kepada yang berbeda agama maupun sukunya di mana misi ini lebih menitik beratkan pada penginjilan kepada yang dapat dijangkau di daerah sekitar orang Kristen Indonesia. Dengan begitu, orang yang diinjili dapat menjadi misionaris yang efektif untuk menjangkau suku maupun suku yang lain. Namun, misiologi diaspora tidak mengabaikan tanggung jawab orang Kristen Indonesia untuk membawa Injil ke tempat yang menjadi tempat diaspora.